Status Report: Development of management, diagnostics and monitoring systems to support the use of regulated non-quarantine weedy wild rice genetic resources for breakthrough innovation in the Philippines - Castellion, Martina (International Rice Research Institute, 2025)
This project was implemented to establish management, diagnostics, and monitoring framework that enables the responsible use of regulated non-quarantine weedy wild rice genetic resources for research and breeding, while safeguarding biosafety, germplasm purity, and surrounding agro-ecosystems in the Philippines. The initiative supports breakthrough innovation by balancing access to valuable wild rice genetic diversity with robust risk-based controls aligned with national regulations and institutional risk appetite. In the Philippines, the management of wild rice is subject to national legal and biosafety obligations, including the Wildlife Resources Conservation and Protection Act of 2001 (Republic Act No. 9147) and the mandates of the National Committee on Biosafety of the Philippines (NCBP) under Executive Order No. 430. These frameworks require that activities involving wild species prioritize ecological balance, biological diversity, and the safe use and containment of biological organisms. Consistent with these requirements, and aligned with the CGIAR Research Ethics Code and IRRI Code of Conduct, researchers and partner institutions are accountable for conducting wild rice-related activities responsibly, transparently, and with due regard to risks to communities and ecosystem. Recognizing both the scientific value and the biosafety risks associated with wild rice, this project aims to establish a risk-based institutional policy framework governing the access, handling, cultivation, movement, monitoring, and disposal of wild rice species and their progenies.